"A Small Story With Great Symbolic Potential": Attempts at Fixing a Cemetery of Unknown Migrants in Tunisia. (April 2020) - Zagaria, Valentina
From the summer of 2015, as Europe faced the so-called "refugee crisis, " a cemetery in southeast Tunisia started gaining fame. Journalists, researchers, filmmakers, photographers, and activists began traveling to the coastal town of Zarzis to report on a burial site for the victims of the European Union's border. They were welcomed by local actors, and in particular by Chamseddine, a former fisherman who over the years became deeply involved in these burials. Told through one man's charitable commitment to provide dignity to those who died at the European Union's liquid border, the cemetery was fixed as a place epitomizing both the deadly effects of migration policies and the compassion of simple citizens in the face of horror. Different individuals and groups also began organizing to materially fix the cemetery. Based on ethnographic fieldwork in Zarzis between 2015 and 2018, this article explores the conceptual and practical acts of "fixing" surrounding the cemetery. These resulted in turning it into a focal symbol triggering moral and political discourses not only of empathy and hope but also of blame and responsibility, bringing to the fore the colonial and neocolonial legacies of the "refugee crisis."